Fire performance of prefabricated modular units using organoclay/glass fibre reinforced polymer composite. (30th December 2016) - Nguyen, Q.T.; Ngo, T.; Tran, P.; Mendis, P.; Zobec, M.; Aye, L.
Abstract: Composite materials like FRPs offer the advantages of the high strength and stiffness with their low density and highly flexible shaping, thus, their potential in replacing conventional materials such as aluminium and steel for prefabrication of modular residential and office applications. The main limitation of fibre reinforced polymer composites (FRPCs) is their relatively poor fire performance. In this study, two CFD models using the modified Mc Grattan and the modified Coats Redfern – Kissinger method were developed to mimic the testing conditions of thermo-gravimetric analysis and cone calorimeter. Validation with experiments proves that the models can realistically predict the fire growth index (FIGRA) and total heat release (THR) of the organoclay/glass fibre reinforced polymer (GFRP) laminates. Two other CFD models were also developed to predict the behaviour of GFRP façade panel, where GFRP laminates are sandwiched with the foam core and undergo ISO 9750-1:2013 conditions in a typical office defined by the National Construction Code, Australia and a city office building in Netherlands. In the first case, 5% organoclay in GFRP prevents flash-over from happening and also the flame from spreading in the horizontal direction. In the second case, organoclay/GFRP panel is tested with different configurations. FIGRAs and THRs in all the selected configurations were found to be well below the thresholds required for building environment. Highlights: We model the burning process of organoclay/GFRP laminates in TGA and Cone Calorimetry. We simulate the organoclay/GFRP as a component of building façade. Inclusion of 5% organoclay in GFRP can prevent flash-over and flame spread. Organoclay/GFRP prefabricated panel is able to meet the building fire requirements.